Assessing the effect of sodium dichloroisocyanurate concentration on transfer of Salmonella enterica serotype Typhimurium in wash water for production of minimally processed iceberg lettuce (Lactuca sativa L.). (1st June 2016) - Maffei, D.F.; Sant'Ana, A.S.; Monteiro, G.; Schaffner, D.W.; Franco, B.D.G.M.
Abstract: This study evaluated the impact of sodium dichloroisocyanurate (5, 10, 20, 30, 40, 50 and 250 mg l −1 ) in wash water on transfer of Salmonella Typhimurium from contaminated lettuce to wash water and then to other noncontaminated lettuces washed sequentially in the same water. Experiments were designed mimicking the conditions commonly seen in minimally processed vegetable (MPV) processing plants in Brazil. The scenarios were as follows: (1) Washing one inoculated lettuce portion in nonchlorinated water, followed by washing 10 noninoculated portions sequentially. (2) Washing one inoculated lettuce portion in chlorinated water followed by washing five noninoculated portions sequentially. (3) Washing five inoculated lettuce portions in chlorinated water sequentially, followed by washing five noninoculated portions sequentially. (4) Washing five noninoculated lettuce portions in chlorinated water sequentially, followed by washing five inoculated portions sequentially and then by washing five noninoculated portions sequentially in the same water. Salm . Typhimurium transfer from inoculated lettuce to wash water and further dissemination to noninoculated lettuces occurred when nonchlorinated water was used (scenario 1). When chlorinated water was used (scenarios 2, 3 and 4), no measurable Salm . Typhimurium transfer occurred if the sanitizer was ≥10 mg l −1 . Use of sanitizers in correct concentrations is important to minimize the risk of microbial transfer during MPV washing. Significance and Impact of the Study: In this study, the impact of sodium dichloroisocyanurate in the wash water on transfer of Salmonella Typhimurium from inoculated lettuce to wash water and then to other noninoculated lettuces washed sequentially in the same water was evaluated. The use of chlorinated water, at concentration above 10 mg l −1, effectively prevented Salm . Typhimurium transfer under several different washing scenarios. Conversely, when nonchlorinated water was used, Salm . Typhimurium transfer occurred in up to at least 10 noninoculated batches of lettuce washed sequentially in the same water.